Norval Morrisseau and the emergence of The Image Makers (Toronto : Art Gallery of Ontario, 1984)
Debassige, Blake ; Kakegamic, Joshim ; Odjig, Daphne ; Ray, Carl ; Thomas, Roy ; Williams, Saul
Norval Morrisseau and the emergence of The Image Makers, Art Gallery of Ontario, Toronto, February 18 - April 15, 1984 ; Thunder Bay National Exhibition Centre and Centre for Indian Art, May 10 - June 17, 1984 ; Chatham Cultural Centre, July 6 - July 29, 1984 ; Art Gallery of Algoma, Sault Ste. Marie, September 20 - Oktober 21, 1984 ; Laurentian University Museum & Arts Centre, Sudbury, December 19, 1984 - January 13, 1985
English
kunstcatalogus
Keywords: Morrisseau, Norval